MORPHOLOGICAL ALTERATIONS OF THE STYLOID PROCESS AND THE CLINICAL SIGNIFICANCE. - HUMBERTO FERREIRA ARQUEZ (International Journal of Pharma and Bio Sciences, 2014)
The elongated styloid process may produce characteristic head and neck pain commonly known as Eagle’s syndrome. The present study was conducted using 25 dry skull and 13 cadavers. The objective was the analysis of the morphological types of styloid process according to Langlais et al. Digital Vernier Callipers was used to measure length, thick of the styloid process. Styloid process had a thickness of 0.45 cm at the base.The average length of the elongated styloid process on the left side was more, compared to right side. Bilateral elongation was more common that the unilateral.78.94% was normal.13.15% having length of 3.5 cm.52.63% having length of 2.5 cm and 39.4% having length of 3.0 cms.7.89% were elongate with average lengths between7.0 and 5.5 cms.An awareness of this syndrome is important to all health practitioners involved in the diagnosis and treatment of neck and head pain.